PENGEMBANGAN KOMIK DIGITAL BERBASIS TRI HITA KARANA UNTUK MENINGKATKAN KETERAMPILAN LITERASI MEMBACA SISWA KELAS IV SEKOLAH DASAR - Ni Putu Sinta Widari; Ni Made Ignityas Prima Astuti; I Made Aditya Dharma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Tri Hita Karana-based digital comic that is feasible, practical, and effective for improving the reading literacy skills of fourth-grade elementary school students. The research method used is Research and Development (R&D), with a development model that includes needs analysis, design, development, implementation, and evaluation. The subjects were fourth-grade elementary school students. Data collection techniques included observation, questionnaires, and reading literacy skills tests. The research instruments included validation sheets from material experts and media experts, teacher and student response questionnaires, and learning outcome tests. The results showed that the Tri Hita Karana-based digital comic achieved a very good level of feasibility, with validation percentages from material experts of 88% and from media experts of 88%, and a practicality level of 88%. The use of digital comics in learning also demonstrated an improvement in the reading literacy skills of fourth-grade elementary school students. Thus, the Tri Hita Karana-based digital comic is deemed suitable for use as a learning medium to improve students' reading literacy skills.